The effect of changes in referral behaviour following NICE guideline publication on agreement of examination findings between professionals in an established glaucoma referral refinement pathway: The Health Innovation & Education Cluster (HIEC) Glaucoma Pathways project. Issue 2 (30th October 2012) - Ratnarajan, Gokulan; Newsom, Wendy; French, Karen; Kean, Jane; Chang, Lydia; Parker, Mike; Garway-Heath, David F; Bourne, Rupert Richard Alexander
Abstract : Aim: To investigate whether the publication of the National Institute for Health and Clinical Excellence (NICE) glaucoma guidelines had an effect on the agreement of examination findings between professionals involved in an established glaucoma referral refinement pathway. Methods: To report inter-professional agreement for the clinical examination findings of optometrists with a special interest in glaucoma (OSI), optometrists with no specialist interest in glaucoma (non-OSI) and a glaucoma consultant. Part 1 investigated agreement between an OSI and consultant and part 2 investigated agreement of clinical findings between the non-OSI and a specialist clinician (OSI or consultant). Results: Part 1: Agreement between OSI and consultant in determining an abnormal intraocular pressure (IOP) (>21 mm Hg) expressed as a percentage positive predictive value (PPPV) was no different pre-NICE (60.6%) and post-NICE (61.4%, p=0.51) guidelines. PPPV for identification of an abnormal optic disc was better pre-NICE (60.6%) than post-NICE (42.7%, p=0.02). The appropriate referral rate for patients referred by an OSI was higher pre-NICE (69.6%) than post-NICE (61.2%) (p=0.07). Part 2: The PPPV between non-OSI and specialist clinician for an abnormal IOP was better pre-NICE (62.5%) than post-NICE (50.9%, p=0.12). This was also observed for abnormal optic discs, 70.0% pre-NICE and 52.9% post-NICE (p=0.04). Conclusions: The accuracy for detecting an abnormal IOP by the OSI has remained unchanged post-NICE, but there was a reduction in accuracy in detecting an abnormal optic disc as well as the appropriate referral rate. For the non-OSI, there was a decline in both IOP and optic disc assessment accuracy.